ANALISIS EFISIENSI PENGGUNAAN KEMBALI AIR LIMBAH PENCUCIAN SARANG BURUNG WALET DI PT. M - Nursari, Savira; Nurhayati; Siregar, Sri RH (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
In the swallow nest production process, the fulfillment of water availability is very important. Water is sourced from the company's Water Treatment Plant (WTP), which is then reprocessed with a Reverse Osmosis (RO) machine. The use of water is sought to be as efficient as possible in the company environment. One way is by recycling wastewater. Wastewater is reused from the swallow nest washing process. RO water results were tested in accordance with the Minister of Health Regulation No. 2 of 2023, while wastewater was tested in accordance with the Minister of Environment Regulation No. 5 of 2014. RO water and wastewater results still meet the required quality standards. The wastewater recycling process uses Ultrafiltration (UF) and RO units. The efficiency of water use is 35.59% and in one year it can save expenses of Rp 135,347,182 / year.